FREQUENCY OF CERVICAL AND INTRACRANIAL ARTERIES LESIONS AND ASSOCIATED CLINICAL SYMPTOMS IN PATIENTS WITH CONFIRMED RENAL FIBROMUSCULAR DYSPLASIA - ARCADIA-POL STUDY. (June 2018) - Swiatlowski, L.; Warchol-Celinska, E.; Kowalczyk, K.; Januszewicz, M.; Florczak, E.; Prejbisz, A.; Jozwik-Plebanek, K.; Michalowska, I.; Witowicz, H.; Kurkowska-Jastrzebska, I.; Adamczak, M.; Pajak, I.; et al.
Abstract : Objective: To assess the frequency of cervical and intracranial arteries involvement and associated clinical symptoms in consecutive patients with renal fibromuscular dysplasia (FMD) enrolled into ARCADIA-POL study. Design and method: From 183 patients with FMD enrolled into ARCADIA-POL study since 2015 (Polish-French collaboration) all consecutive 157 patients (132F, 25 M, mean age:45.1 ± 15.1 years) with renal FMD were analyzed. All patients underwent clinical evaluation: ABPM, biochemical evaluation, biobanking, duplex Doppler of cervical and abdominal arteries and whole body angio-CT including cervical and intracranial arteries. Results: Among 157 patients with renal FMD, 38 (24.2%) had coexisting FMD lesions in cervical and/or intracranial arteries and/or intracranial aneurysms: 17 (10.8%) patients in carotid, 7 (4.5%) patients in vertebral and 24 (15.3%) patients had lesions in intracranial arteries. Dissections of carotid arteries were present in 3 (1.9%) patients and vertebral artery dissections in 3 (1.9%) patients. In 10 (6.4%) pts internal carotid artery aneurysm and in 2 (1.3%) patients vertebral artery aneurysm were found. 18 (11.5%) patients had intracranial aneurysms: 15 (9.6%) patients had one aneurysm, 2 (1.3%) pts 2 aneurysms and 1 (0.6%) patient had 3 aneurysms. Patients with and without cervical and/or intracranial FMD lesions didn't differ in terms of age, gender, clinical and ambulatory blood pressure levels, hypertension prevalence and number of antihypertensive medications. There were no significant differences in the prevalence of symptoms such as headaches, tinnitus, dizziness and cervical bruits between the patients with and without cervical and/or intracranial FMD. There was only a significant difference in the presence of Horner's syndrome between patients with and without cervical and/or intracranial FMD (16.7% vs.1.9%; p = 0.001, respectively). There was no difference in the prevalence of stroke, transient ischemic attack or intracranial bleeding between the groups. Conclusions: There were no specific clinical features suggesting the presence of FMD lesions and vascular complications in cervical and/or intracranial arteries in patients with confirmed renal FMD included into ARCADIA-POL STUDY. Our study showed that systematic evaluation of cervical and intracranial arteries in patients with renal FMD results in revealing relatively high prevalence of FMD lesions and vascular complications in cervical and/or intracranial arteries.